Entrepreneurial Leadership And Sustainable Performance Of Border Agroindustrial MSEMs: The Role Of Human Resources Digital Capabilities And Innovation Capabilities In Sambas Regency - Angga Tritisari; Nur Afifah; Mustaruddin; Titik Rosnani (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of EWOM, social media marketing, and perceived quality on purchase intention through brand image among consumers in Purwokerto. Using a quantitative approach, data was collected from 150 respondents and analyzed using SmartPLS. The results show that EWOM, social media marketing, and perceived quality significantly affect brand image and purchase intention. Brand image also has a positive effect on purchase intention and mediates these relationships. These findings highlight the importance of digital marketing strategies and perceived quality in strengthening brand image and increasing purchase intention. Keywords: Entrepreneurial Leadership; HR Digital Capabilities; Innovation Capabilities; Sustainable Performance; Agro-Industrial MSMEs; SEM-PLS, Border Areas